2014
DOI: 10.1016/j.otsr.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Actifit® synthetic meniscal substitute: Experience with 18 patients in Brest, France

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 6 publications
(6 reference statements)
0
36
0
Order By: Relevance
“…No cases of scaffold separation or meniscal degeneration were recorded in one study, with 50% of patients being able to return to their sporting activities at the time of the two-year followup36). A failure rate of 17.3% was reported in a study assessing polyurethane scaffolds37).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…No cases of scaffold separation or meniscal degeneration were recorded in one study, with 50% of patients being able to return to their sporting activities at the time of the two-year followup36). A failure rate of 17.3% was reported in a study assessing polyurethane scaffolds37).…”
Section: Resultsmentioning
confidence: 96%
“…It is also not well documented whether these meniscus-like scaffolds can transmit the load enough to prevent chondral wear. The main types of meniscal scaffold used were Actifit polyurethane meniscal scaffolds or CMI36,3941,43,49). A phase II feasibility study in eight patients showed new fibrocartilage matrix formation on biopsy tissue and integration into the scaffold was seen on second-look arthroscopy30).…”
Section: Discussionmentioning
confidence: 99%
“…The available short-and long-term studies of clinical outcomes of MAT are variable and difficult to effectively compare due to the heterogeneity of the study population and the availability of treatment techniques 187 . Meniscal allograft transplantation yields fair to excellent results in almost 85% of patients; patients report a significant decrease in pain, as well as an increase in activity [188][189][190][191][192][193] . Meniscal allografts are associated with generally good clinical outcomes, in terms of minimizing radiographic changes, maintaining normal gait and exercise activity and promoting cellular incorporation and tissue healing 150,194 .…”
Section: Results Of Meniscal Transplantsmentioning
confidence: 99%
“…The short-term clinical success of meniscus implantation is very high in these patient groups according to the literature. 10,38,42 However, these methods should be combined with additional procedures that promote healing to shorten the long recovery periods and reduce the problems that patients face when they return to sports. According to our study, CBMA injection in combination with meniscus implantation provides early significant improvement in clinical functions and rapid decrease in the level of pain in our patients.…”
Section: Discussionmentioning
confidence: 99%